Capital Sentencing In Kentucky, 2000–2010 - Vito, Gennaro F. (American journal of criminal justice, 2014)
The current study attempts to build upon previous analyses of capital sentencing in Kentucky and other states. Using data compiled from official court records compiled by the Kentucky Department of Public Advocacy, we examined death eligible homicide cases for the years 2000–2010 for the state ( N = 359). Multivariate analysis determined that the death penalty in Kentucky was sought 3.17 times or 217 % more when the victim is female. It also found that cases featuring a black defendant and a white victim were 56 % less likely to result in a plea than cases featuring other defendant/victim racial combinations. Despite legal requirements, Kentucky fails to collect data to assess the factors that influence the seeking and imposition of the death penalty. Paper presented at the Second Annual Forum on Criminal Law Reform in the Commonwealth of Kentucky on November 15, 2013 at the University of Kentucky Law School, Lexington, KY.